Portfolio ownership in the excess return model at Indonesian stock exchange - Luqman Hakim; Sri Retnaning Sampurnaningsih; Siti Nuraidawati; Aang Aribawa (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This research is to analyze and answer the phenomena of Foreign Portfolio Investment (FK), Global Risk (Rwf), Small minus Big (SmB), High minus Low (HmL), Win minus Lose (WmL) as determinants of Foreign Ownership (FO) which have implications for Excess Return (ER). The formula is to maximize the value of Excess Return through Portfolio Ownership, the object of research for companies on the Indonesia Stock Exchange. First results; an increase in FK can explain the impact on an increase in FO, these results confirm the prevailing theory. Other results are not like the existing theory, namely a decrease in SmB can explain the impact on a decrease in FO, while Rwf, HmL, and WmL cannot explain its effect on FO. Second result; the increase in HmL, WmL and FO can explain the impact of the increase in ER. Another thing FO can also explain its function as an intervening variable. Rwf can also explain the impact but it is not in line with the negative correlation theory. The FK has no impact on ER. These results are expected to help as a guide for foreign investors in the Indonesia Stock Exchange to obtain maximum excess returns.